Avaliação da adesão de Staphylococcus spp. em resina acrílica específica para prótese ocular e alteração de cor de botões de íris artificiais, variando a cor e as técnicas de obtenção, ambos após desinfecção química - Moreno, Amália [UNESP] (2014)
Considering that ocular prostheses restore esthetics and patient’s self-esteem, the materials used for prosthesis fabrication should present appropriate properties regarding indication and reliability after the disinfection procedures. So, the aim of this study was to assess the effectiveness of different disinfectant solutions against two species of Staphylococcus spp. cultured on ocular prosthesis acrylic resin. In addition, the chromatic change of artificial iris buttons fabricated with different techniques was also evaluated before and after polymerization and disinfection. For the microbiology tests 396 acrylic specimens were fabricated (1.0 cm in diameter and 0.3 cm in thickness). Half of the samples were made for biofilm formation of S. epidermidis and half were made for biofilm formation of S. aureus, both on the sample surface. For each strain, 66 samples were underwent to biofilm formation on the liner surface for three different points: initial (24h), intermediate (48h) and mature (72h). Afterwards the specimens were randomly assigned (unit sample n = 6) to one of disinfectant treatments: distilled water for 10, 15, 30 min and 6 h (control-CTL); treated with neutral soap (NES) for 30 min; treated with Opti-Free (OPT) for 30 min and 6 h; treated with Efferdent (EFF) for 15 min; and treated with (0.5%, 2% and 4%) chlorhexidine gluconate (CHX) for 10 min. After the treatments, the specimens were vortexed to disrupt the biofilm, and residual cells were counted (cell/mL). For the color meansurations a total of 300 samples simulating ocular prosthesis were fabricated. Half of the samples were made with blue artificial irises, and half were made with brown artificial irises. For each color, 50 samples were fabricated according to one of the following techniques: PE - conventional technique, CA - prefabricated...